Analisis Efektivitas Biaya Vaksin HPV (Human Papilomavirus) - Lupi Trijayanti; Ascobat Gani (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Cervical cancer can reduce survival which affects productivity, also requires large health insurance payments. Preventive efforts in the form of administering the Human papilloma virus (HPV) vaccine are a long-term investment in preventing new cases of cervical cancer. This study aims to review the literature on the cost-effectiveness of the HPV vaccine in school-age girls. The method used to search for literature is the PICOS framework from national and international journals published from 2021 to 2022 through the Pubmed and ScienceDirect databases. Based on the 3 articles analyzed, the HPV vaccine evaluated by several countries described a significant reduction in the incidence and death from cervical cancer. In addition, HPV vaccination also provides protection against financial risks, namely household expenses caused by this case. From a health standpoint, vaccination can reduce DALYs and improve quality of life in a healthy and perfect condition. HPV vaccination is a preventive program which is a long-term and cost-effective investment for handling new cases if the coverage of vaccination is high enough.Keywords: cervical cancer; Human papilloma virus; vaccine; cost effectiveness ABSTRAK Kanker serviks dapat menurunkan ketahanan hidup yang mempengaruhi produktifitas, juga membutuhkan pembayaran jaminan kesehatan yang besar. Upaya preventif berupa pemberian vaksin Human papiloma virus (HPV) merupakan investasi jangka panjang dalam mencegah kasus baru kanker serviks. Studi ini bertujuan untuk mereview literature tentang efektifitas biaya vaksin HPV pada anak perempuan usia sekolah. Metode yang digunakan untuk mencari literatur adalah PICOS framework dari jurnal nasional dan internasional yang diterbitkan tahun 2021 sampai 2022 melalui database Pubmed dan ScienceDirect. Berdasarkan 3 artikel yang dianalisis, vaksin HPV yang dievaluasi oleh beberapa negara menggambarkan adanya penurunan insiden dan kematian akibat kanker serviks secara signifikan. Selain itu, vaksinasi HPV juga memberikan perlindungan terhadap risiko keuangan yaitu pengeluaran rumah tangga yang disebabkan oleh kasus ini. Dari sisi kesehatan, vaksinasi dapat menurunkan DALYs dan meningkatkan kualitas hidup dalam kondisi sehat dan sempurna. Vaksinasi HPV merupakan program preventif yang merupakan investasi hemat jangka panjang dan efektif dari segi biaya untuk penanganan kasus baru bila jangkauan dari vaksinasi cukup tinggi. Kata kunci: kanker serviks; Human papiloma virus; vaksin; efektivitas biaya